Oestro synchronization with cloprostenol. Influences on progesterone levels on days 17th – 23rd of pregnancy (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1989)
Sixteen non-pregnant Holstein-Gir cross bred cows were separated in two groups: Group A – 10 oestrous synchronized cows with double doses of 0.25 mg of cloprostenol, and group B – 6 spontaneous-oestrous detected cows. Three animals from group A did not show any signs of oestrous and the cowsn n° 10 and 13 were isolated from the herd. The remaining animals were inseminated. Plasma progesterone levels were determined by a solid phase radioimmunoassay on days 17, 20 and 23 after artificial insemination (AI). Seventy percent of synchronized animals showed oestrous until 7 days after the last administration of cloprostenol and sixty percent became pregnant. No statistical difference between non synchronized and synchronized pregnant cows on days 17, 20 and 23 after A.I. was found.